Antibody or Antibody Fragments: Implications for Molecular Imaging and Targeted Therapy of Solid Tumors - Xenaki, Katerina T.; Oliveira, Sabrina; van Bergen en Henegouwen, Paul M. P. (Frontiers in Immunology, 2017)
Abstract The use of antibody-based therapeutics has proven very promising for clinical applications in cancer patients, with multiple examples of antibodies and antibody-drug conjugates successfully applied for the treatment of solid tumors and lymphomas. Given reported recurrence rates, improvements are clearly still necessary. A major factor limiting the efficacy of antibody-targeted cancer therapies may be the incomplete penetration of the antibody or antibody-drug conjugate into the tumor. Incomplete tumor penetration also affects the outcome of molecular imaging, when using such targeting agents. From the injection site until they arrive inside the tumor, targeting molecules are faced with several barriers that impact intratumoral distribution. The primary means of antibody transport inside tumors is based on diffusion. The diffusive penetration inside the tumor is influenced by both antibody properties, such as size and binding affinity, as well as tumor properties, like microenvironment, vascularisation and targeted antigen availability. Engineering smaller antibody fragments has shown to improve the rate of tumor uptake and intratumoral distribution. However, it is often accompanied by more rapid clearance from the body and in several cases also by inherent destabilization and reduction of the binding affinity of the antibody. In this perspective, we discuss different cancer targeting approaches based on antibodies or their fragments. We carefully consider how their size and binding properties influence their intratumoral uptake and distribution, and how this may affect cancer imaging and therapy of solid tumors.